Inhibition of Food- Borne Pathogens by Pediococcus Pentosaceus DS1 and in Silico Analysis of the Pediocin Gene: Life Science-Biotechnology - Loying, Surjya; Prakash Parasar, Deep; Nayak, Rahul; Pratim kashyap, Manash; Saikia, Devabrata (International Journal of Life Science and Pharma Research, 2022)
Global food safety is a huge concern, costing food industries billions of dollars every year. A healthy eating habit has become a myth due to an increase in food borne diseases. It is therefore necessary to avoid economic losses due to microbial spoilage and to preserve foods naturally in order to solve many of the current issues with food. Antimicrobial peptides isolated from bacteria have garnered considerable attention because of their potential benefits in extending the shelf-life of food products. Listeria monocytogenes and Staphylococcus aureus are two opportunistic pathogens which cause various food borne diseases. The aim of the study was to evaluate the production of antimicrobial compounds by the strain Pediococcus pentosaceus DS1 isolated from ekung, a fermented bamboo shoot product of North- East India. The main objectives of the study were to perform agar well diffusion assay for antimicrobial activity followed by characterization of the antimicrobial compound present in the cell free supernatant of the bacteria. It was observed that the antimicrobial peptide containing cell surface supernatant extracted from P. pentosaceus DS1 was able to inhibit Listeria monocytogenes (MTCC 839) and Staphylococcus aureus (MTCC 3160). PCR amplification led to the detection of a gene sequence in the genome of the strain P. pentosaceus DS1 which showed maximum similarity to pediocin, a 406 bp sequence. Pediocin belongs to a group of antimicrobial proteins known as bacteriocins which possess antimicrobial activities against food borne pathogens and spoilage bacteria. In- silico analysis indicated the presence of class IIa bacteriocin superfamily motif in the sequence. Class IIa bacteriocin producing bacteria isolated from fermented foods have a proven history of being used safely as antimicrobial agents in the food industry. Thus, this study reveals that P. pentosaceus DS1 has the potential to produce bacteriocinogenic agents that can be used safely to inhibit food pathogens